Beyond Financial Growth: Do Governance and Profitability Drive Sustainability Transparency? - Dinda Rahmawaty; Rista Bintara (Tazkia Islamic University College, 2026)
Amidst increasing regulatory pressure for corporate accountability, sustainability reporting has become a strategic imperative for the energy sector. This study investigates the impact of profitability, institutional ownership, audit committee effectiveness, and firm size on sustainability report disclosure among energy companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. Using a purposive sampling technique, a longitudinal dataset of 40 observations from 8 representative firms was analyzed. Data processing was conducted via multiple linear regression analysis. The empirical results demonstrate that profitability, audit committee, and firm size exert a significant positive influence on the extent of sustainability disclosure. Conversely, institutional ownership was found to have a negative effect. These findings underscore that internal corporate governance mechanisms and financial capacity are primary drivers in enhancing transparency and stakeholder accountability. This research provides practical insights for regulators and investors regarding the non-financial reporting landscape in high-impact industries.